Corporate Social Responsibility (CSR) and Stakeholders Reaction: A Survey on Impact of CSR on Firm Performance in Gujarat (Global Journal of Management and Business Research, 2017)
CSR has been major component for the welfare of society. This study examines whether corporate social responsibility (CSR) towards primary stakeholders influences the financial and the non-financial performance (NFP) of Indian firms. Data on CSR were collected from 25 senior-level managers including CEOs through questionnaire survey. Hard data on financial performance (FP) of the companies were obtained from secondary sources. A questionnaire for assessing CSR was developed with respect to six stake holder groupsemployees, suppliers, customers, society at large. A compo site measure of CSR was obtained by aggregating the six dimensions. This study aims to obtain information about the impact of CSR activities on performance of an organization. In today's society, there is a growing interest in, and demand for Corporate Social Responsibility (CSR).
Keywords: foreign investment; FDI (foreign direct investment); FII (foreign institutional investment) and sensex